Pancasila as the Foundation of the State: An Analysis of Values and Principles in Building the Character of Elementary School Students (Grade 1) at SDN 001 Sangatta Utara - Farida Catur Wahyu Anggriyani; Nur Afni Pratiwi; Dwi Meli Noviani (Penerbit Hellow Pustaka, 2025)
Pancasila as the basis of the Indonesian state plays an important role in shaping the nation's character, including in education at the elementary level. This article aims to analyze the implementation of Pancasila values ​​and principles in building the character of grade 1 SD/MI students at SDN 001 Sangatta Utara. This research uses a qualitative approach with a case study method, which involves observation, interviews with teachers, and document analysis. The results of the research show that the application of Pancasila values ​​in learning in class 1 of SDN 001 Sangatta Utara has a positive impact on the development of students' character, which is reflected in religious attitudes, mutual respect and mutual cooperation. However, challenges such as limited time and learning media are obstacles to its implementation. This research recommends the importance of strengthening Pancasila education more systematically to shape national character from an early age.